Effects of external mechanical or magnetic fields and defects on electronic and transport properties of graphene - Radchenko, Taras M.; Tatarenko, Valentyn A.; Cuniberti, Gianaurelio (Giovanni) (Materials Today: Proceedings, 2019)
We report on the results obtained modelling the electronic and transport properties of single-layer graphene subjected to mechanical or magnetic fields and containing point defects. Reviewing, analyzing, and generalizing our findings, we claim that effects of uniaxial tensile strain or shear deformation along with their combination as well as structural imperfections (defects) can be useful for achieving the new level of functionalization of graphene, viz. for tailoring its electrotransport properties via tuning its band gap value as much as it is enough to achieve the graphene transformation from the zero-band-gap semimetal into the semiconductor and even reach the gap values that are substantially higher than for some materials (including silicon) typically used in nanoelectronic devices.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Band gap; Defects; Graphene; Magnetic field; Strain